Real time monitoring of spot-welded joints under service load using lead zirconate titanate (PZT) transducers. (21st February 2017) - Yao, Ping; Zheng, Botong; Dawood, Mina; Huo, Linsheng; Song, Gangbing
Abstract: This paper proposes a nondestructive method to evaluate the health status of resistance spot-welded (RSW) joint under service load using lead zirconate titanate (PZT) active sensing system, in which the PZT transducers were used as both actuator and sensor. The physical principle of the approach was validated through a numerical analysis showing that an opening between the faying faces at the welded joint occurred under tension load. The opening decreased the contact area hence reduced the amplitude of the stress wave received by the PZT sensor. Therefore, by comparing the energy index of the signals before and after the loading, the health condition of the joint can be evaluated. Five ST14 steel single lap joint specimens were tested under tension load while being monitored by the PZT sensing system and digital image correlation (DIC) system in real time. The data obtained from the DIC system validated the numerical results. By comparing the energy index of the signal obtained from the PZT sensing system before and after unloading, it was concluded that the RSW joint was intact after being loaded to the service load. The proposed method is promising in evaluating the health condition of RSW joint nondestructively.